Handbook of Research on Machine Learning Applications and Trends 2010
DOI: 10.4018/978-1-60566-766-9.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Learning

Abstract: Transfer learning is the improvement of learning in a new task through the transfer of knowledge from a related task that has already been learned. While most machine learning algorithms are designed to address single tasks, the development of algorithms that facilitate transfer learning is a topic of ongoing interest in the machine-learning community. This chapter provides an introduction to the goals, settings, and challenges of transfer learning. It surveys current research in this area, giving an overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
760
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,486 publications
(879 citation statements)
references
References 0 publications
4
760
0
14
Order By: Relevance
“…For such single and multiagent tasks, policy transfer is typically done within the same task domain for varying task complexity (Torrey and Shavlik, 2009) and less frequently between different task domains (Bou-Ammar et al, 2015). Recently, there has been work investigating the efficacy of using policy transfer in company with Evolutionary Algorithms (EAs) (Eiben and Smith, 2003) to boost evolved solution quality of evolved genotypes with various representations.…”
Section: Evolutionary Policy Transfermentioning
confidence: 99%
“…For such single and multiagent tasks, policy transfer is typically done within the same task domain for varying task complexity (Torrey and Shavlik, 2009) and less frequently between different task domains (Bou-Ammar et al, 2015). Recently, there has been work investigating the efficacy of using policy transfer in company with Evolutionary Algorithms (EAs) (Eiben and Smith, 2003) to boost evolved solution quality of evolved genotypes with various representations.…”
Section: Evolutionary Policy Transfermentioning
confidence: 99%
“…It has been empirically and theoretically shown that transfer learning can greatly improve the learning performance especially when only a small number of data are available in a target domain [3], [4]. Speech emotion recognition can benefit from using transfer learning as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transfer learning has been proposed to develop methods to transfer useful information in one or more source tasks to a related target task [3]. It has been empirically and theoretically shown that transfer learning can greatly improve the learning performance especially when only a small number of data are available in a target domain [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of instance transfer depends on the relevance of the source domain to the target domain [19]. Since the distributions of the domains are usually unknown, the relevance can be estimated by the relevance of the source data to the target data.…”
Section: Introductionmentioning
confidence: 99%